ISSUES OF DEVELOPMENT OF FLUENT SPEECH OF PRESCHOOL CHILDREN BASED ON A VARIATIONAL APPROACH (E Global Congress, 2023)
In this article, the development of the fluent speech of preschool children, its goals and tasks, the inseparableness of speech from the world of thoughts, fluent speech is the fluency of thoughts, in which the child's ability to think logically, reflect on what he perceives and express them correctly information has been given.